Khả năng bảo vệ chống ăn mòn của màng nano-compozit Ppy/-Fe2O3 được tổng hợp điện hóa khi có mặt các chất hoạt động bề mặt - Lê Hiền và cộng sự, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Electrosynthezation processe of Ppy/a-Fe2O3 nano-composite films on the iron have been investigated in solution containing potassium tetraoxalate, pyrrole and nano a-Fe2O3 in suspension with and without surfactants. The film formed in solution with dodecylsulfate anionic surfactant gives the best results of protection against corrosion of iron. This film can protect metal in NaCl 3% corrosion solution during 370 hours, two times longer than which formed in solution with cetyl trimethyl amonium cationic surfactant and five times longer than polypyrrole film without nano-oxide.